Genotype by Environment Interaction Effects on Nutraceutical Lipid Compounds of Pigmented Rice (Oryza sativa L. ssp. indica) - Bhornchai Harakotr; Kasidid Prompoh; Khundej Suriharn; Kamol Lertrat (International Journal of Agronomy)
To identify a rice genotype with a wider or specific adaptability, the magnitude and patterns of genotype interaction with the environment are valuable clues. However, such information on the nutraceutical lipid compound in rice is limited. In this study, concentrations of five pigmented rice genotypes with different lipid compound levels were evaluated for α-tocopherol, γ-oryzanol, phytosterols, octacosanol, and squalene contents. The research was conducted in eight environments (four locations and two years). Combined analysis of variance showed that levels of α-tocopherol, γ-oryzanol, octacosanol, and squalene were mainly affected by genotype, accounting for more than 42.57% of the total variance. This suggests that improvement of these traits may be achieved by using conventional rice breeding methods. A large proportion of the variation in campesterol and β-sitosterol contents was contributed by the environment. The effect of genotype by environment was significant for all observed traits, especially for γ-oryzanol, β-sitosterol, and squalene. This complicates identification of superior genotypes for these compounds across all environments. Stability parameters showed rice genotypes with high levels of nutraceutical lipid compounds to be sensitive to changes in environmental conditions; thus, specific adaptation is suitable. Our findings suggest that rice breeders and producers should be testing and selecting rice genotypes possessing high added-value lipid concentrations in specific growing conditions or regions.